Impact of Comorbidities on Survival Among Patients with Chronic Myeloid Leukaemia Using the Charlson Comorbidity Index: Retrospective study from Basra, Iraq - Abood, Rafid A. (Sultan Qaboos Univ Med J, 2019)
OBJECTIVES: In chronic diseases, comorbidities are known to have a strong negative association with overall survival (OS). This study aimed to use the Charlson Comorbidity Index (CCI) to examine the effect of comorbidities on OS among patients with chronic myeloid leukaemia (CML) treated with tyrosine kinase inhibitors. METHODS: This retrospective study was conducted between January 2006 and October 2016 and included 247 CML patients treated at the Basra Oncology & Haematology Centre, Basra, Iraq. Information from hospital records was used to calculate CCI scores and patients were divided into groups based on scores of 2–3 (CCI1 group) or ≥4 (CCI2 group). The OS was calculated using Kaplan-Meier curves. RESULTS: There were 177 (71.7%) patients in the CCI1 group and 70 (28.3%) in the CCI2 group. Overall, patients in the CCI1 group were significantly younger compared to those in the CCI2 group (median age: 35 versus 60 years; P <0.001); however, the gender distribution was similar in both groups (male-to-female ratio of 1:1.06 versus 1:1.18, respectively; P = 0.683). Diabetes mellitus was the most common comorbidity (17%), followed by hypertension (12%) and gastrointestinal diseases (6%). There were no significant differences in mortality between the groups (9.6% versus 8.6%; P = 0.801). In total, 69.6% of all deaths were related to CML progression rather than to the presence of comorbidities. CONCLUSION: No significant correlation was found between CCI score and OS among CML patients in Basra. However, larger long-term prospective studies are needed to evaluate associations with median age at diagnosis and disease severity and to develop region-specific prognostic scales.